Deferoxamine Treatment Improves Antioxidant Cosmeceutical Formulation Protection against Cutaneous Diesel Engine Exhaust Exposure - Erika Pambianchi; Francesca Ferrara; Alessandra Pecorelli; Mascia Benedusi; Hina Choudhary; Jean-Philippe Therrien; Giuseppe Valacchi (Antioxidants, 2021)
Skin is one of the main targets of the outdoor stressors. Considering that pollution levels are rising progressively, it is not surprising that several cutaneous conditions have been associated with its exposure. Among the pollutants, diesel engine exhaust (DEE) represents one of the most toxic, as it is composed of a mixture of many different noxious chemicals generated during the compression cycle, for ignition rather than an electrical spark as in gasoline engines. The toxic chemicals of most concern in DEE, besides the oxides of nitrogen, sulfur dioxide and various hydrocarbons, are metals that can induce oxidative stress and inflammation. The present study aimed to evaluate the effects of topical application, singularly or in combination, of the iron-chelator deferoxamine and a commercially available formulation, CE Ferulic, in up to 4-day DEE-exposed skin. DEE induced a significant increase in the oxidative marker 4-hydroxy-nonenal (4HNE) and matrix-metallopeptidase-9 (MMP-9), the loss of cutaneous-barrier-associated proteins (filaggrin and involucrin) and a decrease in collagen-1, while the formulations prevented the cutaneous damage in an additive manner. In conclusion, this study suggests that iron plays a key role in DEE-induced skin damage and its chelation could be an adjuvant strategy to reinforce antioxidant topical formulations.